THE ROLE OF WORDS WITH A LIMITED SCOPE IN THE SPEECH PROCESS - Tajiyeva Zuhra Kamalbaevna (Scholar Express Journal, 2024)
This article discusses the features of the use of words in the speech of the limited vocabulary of the modern Russian language, which is widely used for stylistic purposes: terms, professionalisms, jargonisms, dialectisms, etc. Examples are given in which the features of the use of limited vocabulary in speech are determined.
Keywords: Words of limited vocabulary; terms; professionalisms